The identification of dwellings and site formation processes at archaeological settlements in the tropics: A micro-geoarchaeological case study from neolithic Loc Giang, southern Vietnam. (1st September 2022) - Grono, Elle; Piper, Philip J.; Nguyen, Khanh Trung Kien; Dang, Ngoc Kinh; Denham, Tim; Friesem, David E.
Abstract: Across the prehistoric period in Mainland Southeast Asia (MSEA), very few architectural remains and settlements have been identified and there is an absence of evidence for dwellings and domestic spaces. Loc Giang (3980–3270 cal BP) in Long An Province, southern Vietnam is one of the few prehistoric settlements excavated in the region, revealing compacted, laterally extensive layers hypothesised to be floors in association with several other occupation deposit types. Due to the complex occupation stratigraphy encountered in the field, as well as intensive post-depositional processes of tropical environments, a state-of-the-art micro-geoarchaeological approach was used to identify site formation processes. Here, we present a description and depositional history of eight major deposit types (microfacies); among these, we identify constructed lime mortar floors, pile dwellings, evidence for the systematic treatment of waste, and prepared organic deposits likely associated with the management of dog and pig populations. Through the study of site formation we reconstruct at high resolution the nature of dwellings and organisation of domestic spaces within one of the earliest neolithic and sedentary settlements in the region. We demonstrate that within destructive burial environments of the tropics, micro-geoarchaeology offers an effective scientific toolkit for detecting settlement features with low macro-archaeological visibility, thereby enabling us to reconstruct pile dwellings and associated lime floors that were poorly characterised previously in MSEA prehistory. Highlights: First micro-geoarchaeological study of a prehistoric settlement in Mainland Southeast Asia (MSEA). Micro-geoarchaeology identifies pyrogenic lime mortar floors and pile dwellings. Differential preservation of construction materials result from tropical post-depositional processes. Early evidence (3510–3150 cal BP) for substantial dwellings and sedentism in MSEA. Micro-geoarchaeology reconstructs the settlement record formerly missing in MSEA.